Academic Integration of Mainland Chinese Students in Germany - Li, Hanwei (Social Inclusion, 2017)
This article presents an analysis of the academic integration experiences of mainland Chinese tertiary-level students in Germany. Using Tinto’s model, the article explores the challenges that Chinese students face during their academic integration, the strategies they employ, and the relationship between academic and social integration. The data were collected in spring 2016 by interviewing 26 mainland Chinese students studying either in German universities or universities of applied sciences. Four major challenges were identified and analyzed: language barrier, knowledge gap, pedagogical differences, and cultural differences. An important outcome of the study presented is that social integration serves as a facilitator for enhancing academic integration, but is not a prerequisite for academic success. Group learning with peers was found to enhance learning outcomes. Overall, Chinese students have exploited their own advantages in academic integration by exploring feasible strategies and benefiting from their past learning experiences. It is suggested that academic integration as a long and challenging process for international students should be acknowledged by the German HEIs, and that more institutional support and guidance are needed.